Diclofenac Salts, VIII. Effect of the Counterions on the Permeation through Porcine Membrane from Aqueous Saturated Solutions - Cristina Cavallari; Annamaria Monastero; Glenda Bassini; Adamo Fini (MDPI AG, 2012)
The following bases: monoethylamine (EtA), diethylamine (DEtA), triethylamine (TEtA), monoethanolamine (MEA), diethanolamine (DEA), triethanolamine (TEA), pyrrolidine (Py), piperidine (Pp), morpholine (M), piperazine (Pz) and their N-2-hydroxyethyl (HE) analogs were employed to prepare 14 diclofenac salts. The salts were re-crystallized from water in order to obtain forms that are stable in the presence of water. Vertical Franz-type cells with a diffusional surface area of 9.62 cm2 were used to study the permeation of these diclofenac salts from their saturated solutions through an internal pig ear membrane. The receptor compartments of the cells contained 100 mL of phosphate buffer (pH 7.4); a saturated solution (5 mL) of each salt was placed in the donor compartment, thermostated at 37 °C. Aliquots were withdrawn at predetermined time intervals over 8 h and then immediately analyzed by HPLC. Fluxes were determined by plotting the permeated amount, normalized for the membrane surface area versus time. Permeation coefficients were obtained dividing the flux values J by the concentration of the releasing phase-that is, water solubility of each salt. Experimental results show that fluxes could be measured when diclofenac salts with aliphatic amines are released from a saturated aqueous solution. Different chemical species (acid, anion, ion pairs) contribute to permeation of the anti-inflammatory agent even though ion-pairs could be hypothesized to operate to a greater extent. Permeation coefficients were found higher when the counterion contains a ring; while hydroxy groups alone do not appear to play an important role, the ring could sustain permeation, disrupting the organized domains of the membrane.